Financing Vietnam’s North-South High-Speed Railway: A Comparative Analysis of International Models and a Proposed Framework - Le, Thi Yen Vi; Nguyen, Tien Thuy (Tạp chí Khoa học Công nghệ Giao Thông Vận Tải, 2026)
This paper examines appropriate financial strategies for the development of high-speed rail (HSR) projects, with particular attention to designing a feasible and resilient financing framework for Vietnam’s proposed North-South HSR. Drawing on comparative case studies of Japan, China, South Korea, France, Germany, and Spain, the study analyzes the capital mobilization structures, governance models, and risk-sharing arrangements that have shaped both positive and problematic outcomes in international HSR development. The research evaluates critical determinants of financial viability, including infrastructure costs, demand projections, and the socio-economic impacts of improved connectivity, labor mobility, and urban regeneration. Based on comprehensive international comparative analysis and Vietnam’s specific constraints, this paper proposes a modified state-led financing model with state capital at 85.27% of total investment and carefully structured 14.73% private sector participation. The framework integrates land value capture mechanisms, diversified funding sources, and institutional safeguards aimed at ensuring fiscal sustainability, operational efficiency, and long-term developmental benefits. The findings provide actionable policy recommendations for Vietnam’s HSR financing strategy, emphasizing the importance of corridor differentiation, phased implementation, transparent risk allocation, and lifecycle funding discipline